2013
DOI: 10.1210/en.2012-1628
|View full text |Cite
|
Sign up to set email alerts
|

Tetrac Can Replace Thyroid Hormone During Brain Development in Mouse Mutants Deficient in the Thyroid Hormone Transporter Mct8

Abstract: The monocarboxylate transporter 8 (MCT8) plays a critical role in mediating the uptake of thyroid hormones (THs) into the brain. In patients, inactivating mutations in the MCT8 gene are associated with a severe form of psychomotor retardation and abnormal serum TH levels. Here, we evaluate the therapeutic potential of the TH analog 3,5,3',5'-tetraiodothyroacetic acid (tetrac) as a replacement for T(4) in brain development. Using COS1 cells transfected with TH transporter and deiodinase constructs, we could sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 57 publications
1
59
0
Order By: Relevance
“…D, deiodinase; MAO, monamine oxidase; SSAO, semicarbazide-sensitive amine oxidase; ODC, ornithine decarboxylase; TK 3 , 3,3′,5-triiodothyropyruvic acid. Horn et al 2013). TA 3 is even a better substrate for D1 than T 3 , illustrated by a 16-fold higher Vmax/Km ratio (Rutgers et al 1989a).…”
Section: Figurementioning
confidence: 96%
“…D, deiodinase; MAO, monamine oxidase; SSAO, semicarbazide-sensitive amine oxidase; ODC, ornithine decarboxylase; TK 3 , 3,3′,5-triiodothyropyruvic acid. Horn et al 2013). TA 3 is even a better substrate for D1 than T 3 , illustrated by a 16-fold higher Vmax/Km ratio (Rutgers et al 1989a).…”
Section: Figurementioning
confidence: 96%
“…Evidence from in vitro and in vivo studies have demonstrated the important role of thyroid hormones in brain development. In cerebellar cell cultures, dendritic growth of Purkinje cells was significant in the presence of T3 or T4, but not in the absence of thyroid hormones (3,4). In rats, studies have demonstrated the structural and functional consequences of maternal thyroid dysfunction on the fetal brain including alterations in the neuronal proliferation, migration, differentiation, synaptogenesis and myelination (1,2,5).…”
Section: Introductionmentioning
confidence: 99%
“…Although some of them were shown to have beneficial effects in Mct8 KO zebrafish larvae (Zada et al 2014) and in Mct8/Oatp1c1 double KO mice (Horn et al 2013, Kersseboom et al 2014, a recent clinical trial in patients treated in the first year of infancy failed to improve mental status, probably because neurological damage was already irreversible at the onset of treatment (Verge et al 2012). A better understanding of the function of MCT8 at the neuronal level during embryonic development is therefore an important objective.…”
Section: Introductionmentioning
confidence: 99%